2022
DOI: 10.3389/fimmu.2022.978429
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of tacrolimus on top of glucocorticoids in the management of IIM-ILD: A retrospective and prospective study

Abstract: ObjectiveTo examine the efficacy of tacrolimus on top of glucocorticoids (GCs) in the management of idiopathic inflammatory myopathies-associated interstitial lung disease (IIM-ILD) and further assess the therapeutic benefit and safety of low-dose pirfenidone followed above treatments.MethodsThe retrospective study comprised 250 patients with IIM-ILD hospitalized in Tongji Hospital from 2014 to 2020. Demographic data, survival outcomes, and recurrence rates over the 1-year follow-up period were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Many studies using TAC for IIM targeted a trough of 5 to 10 ng/mL. 155,157,158,160,161 However, in our practice, we find maintaining a more conservative trough of 3 to 6 ng/mL achieves excellent disease control with a more favorable side-effect profile.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 65%
“…Many studies using TAC for IIM targeted a trough of 5 to 10 ng/mL. 155,157,158,160,161 However, in our practice, we find maintaining a more conservative trough of 3 to 6 ng/mL achieves excellent disease control with a more favorable side-effect profile.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 65%
“…RP‐ILD carries a substantial risk of death, and several observational studies have suggested benefit from treatment with upfront combination therapy 12,100–102,108,111–113 . A study of MDA‐5‐ILD evaluating combination cyclophosphamide, tacrolimus, and glucocorticoids demonstrated a beneficial effect on survival compared to a sequential step‐up approach 12 .…”
Section: Results/recommendationsmentioning
confidence: 99%
“…RP-ILD carries a substantial risk of death, and several observational studies have suggested benefit from treatment with upfront combination therapy. 12,[100][101][102]108,[111][112][113] A study of MDA-5-ILD evaluating combination cyclophosphamide, tacrolimus, and glucocorticoids demonstrated a beneficial effect on survival compared to a sequential step-up approach. 12 One study found adding IVIG to standard immunosuppressive medications in MDA-5 RP-ILD resulted in lower all-cause death rate compared with standard therapy.…”
Section: Recommendations For Management Of Sard With Rp-ildmentioning
confidence: 99%
“…RP‐ILD carries a substantial risk of death, and several observational studies have suggested benefit from treatment with upfront combination therapy 12,99–101,107,110–112 . A study of MDA‐5‐ILD evaluating combination cyclophosphamide, tacrolimus, and glucocorticoids demonstrated a beneficial effect on survival compared to a sequential step‐up approach 12 .…”
Section: Results/recommendationsmentioning
confidence: 99%
“…RP-ILD carries a substantial risk of death, and several observational studies have suggested benefit from treatment with upfront combination therapy. 12,[99][100][101]107,[110][111][112] A study of MDA-5-ILD evaluating combination cyclophosphamide, tacrolimus, and glucocorticoids demonstrated a beneficial effect on survival compared to a sequential step-up approach. 12 One study found adding IVIG to standard immunosuppressive medications in MDA-5 RP-ILD resulted in lower all-cause death rate compared with standard therapy.…”
Section: Recommendations For Management Of Sard With Rp-ildmentioning
confidence: 99%